Murabahah Working Capital and Investment Financing in Increasing Business Income: Pembiayaan Modal Kerja dan Investasi Murabahah dalam Meningkatkan Pendapatan Usaha - Sri Ayu Fadhilah; Tuti Anggraini; Juliana Nasution (Academia Open, 2025)
General Background: The Islamic banking industry plays a pivotal role in financial inclusion, particularly for micro, small, and medium enterprises (MSMEs), through Sharia-compliant financing schemes. Specific Background: PT BPRS Puduarta Insani Medan Tembung, as a regional Sharia microfinance institution, actively distributes working capital and investment financing using murabahah contracts. Knowledge Gap: However, empirical studies examining the direct impact of such financing on community business income, especially within localized contexts like Medan Tembung, remain limited. Aims: This study investigates how working capital and investment financing under murabahah contracts affect the business performance of local MSMEs. Results: Findings show a positive correlation between murabahah-based financing and increased business income, improved financial capacity, and enhanced operational performance among recipients. Novelty: The study provides in-depth qualitative evidence on the effective implementation of murabahah bi al-wakalah contracts in grassroots banking operations, emphasizing customer empowerment and Sharia adherence. Implications: These insights support policy and institutional strategies aimed at expanding Sharia-based financial services, reducing poverty, and promoting sustainable regional economic growth through inclusive Islamic finance mechanisms.Highlight : Working capital and investment financing using murabahah contracts significantly increased MSME income in Medan Tembung. PT BPRS Puduarta Insani’s financing strategy aligns with national goals for Islamic banking growth and inclusion. Murabahah bi al-wakalah structure ensures sharia compliance and operational simplicity for both bank and customers. Keywords : Working Capital Financing, Investment Financing, Murabahah Contract, Business Income, Islamic Microfinance